OPTIMALISASI PERAN TEKNOLOGI INFORMASI (INTERNET) DALAM MENINGKATKAN EFEKTIFITAS DAN KUALITAS PROSES PEMBELAJARAN PJJ S1 PGSD - Ariyawan Agung Nugroho (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Government’s program to improve elementary school or MI teachers’ qualification has been highly well responded by society. The teachers whose qualification is not yet equal to S1 degree are enthusiastically attending program of distance learning S1 PGSD held by 10 universities or Teacher Education Institutes (LPTK). Educational Science Faculty (FIP), Yogyakarta State University (UNY) is one of the LPTKs entrusted to conduct the program. In so doing, FIP has been implementing a distance learning system named Flexible Learning Model which requires web or internet support in carrying out the learning process.Yet, deemed as having web-based and blended learning system and model, the conduct of distance learning held by FIP is not as expected. The use of web is limited to e-mail leaving the other internet or web facilities. Moreover, FIP’s distance learning does not embrace interaction using online discussion forum which enables teachers and student to directly communicate at the same time (synchronous). This might lead to ineffective and less quality distance learning practice which in the end might bring about a less qualified graduate (read: teacher) since internet has been the most prominent support in determining the quality of interaction and learning process between teacher and student in distance learning program. Without optimal and effective use of internet, student and teacher cannot interact well and effectively.To this point, this paper aims to propose an alternative by designing and creating a particular website serving as the supporting software or Learning Management System media, providing a learning activity center, synchronous and asynchronous mode of student – teacher and student – student interaction, academic and administration information center, reviewing and testing media, digital library and e-material enabling student and teacher to independently learn. In addition, a website particularly designed in such a way to address needs and the characteristics of the Faculty’s distance learning program will certainly benefit the teacher in that it provides a record of all teaching and learning activitues conducted through web, which functions as a portofolio.Government’s program to improve elementary school or MI teachers’ qualification has been highly well responded by society. The teachers whose qualification is not yet equal to S1 degree are enthusiastically attending program of distance learning S1 PGSD held by 10 universities or Teacher Education Institutes (LPTK). Educational Science Faculty (FIP), Yogyakarta State University (UNY) is one of the LPTKs entrusted to conduct the program. In so doing, FIP has been implementing a distance learning system named Flexible Learning Model which requires web or internet support in carrying out the learning process.Yet, deemed as having web-based and blended learning system and model, the conduct of distance learning held by FIP is not as expected. The use of web is limited to e-mail leaving the other internet or web facilities. Moreover, FIP’s distance learning does not embrace interaction using online discussion forum which enables teachers and student to directly communicate at the same time (synchronous). This might lead to ineffective and less quality distance learning practice which in the end might bring about a less qualified graduate (read: teacher) since internet has been the most prominent support in determining the quality of interaction and learning process between teacher and student in distance learning program. Without optimal and effective use of internet, student and teacher cannot interact well and effectively.To this point, this paper aims to propose an alternative by designing and creating a particular website serving as the supporting software or Learning Management System media, providing a learning activity center, synchronous and asynchronous mode of student – teacher and student – student interaction, academic and administration information center, reviewing and testing media, digital library and e-material enabling student and teacher to independently learn. In addition, a website particularly designed in such a way to address needs and the characteristics of the Faculty’s distance learning program will certainly benefit the teacher in that it provides a record of all teaching and learning activitues conducted through web, which functions as a portofolio.